2009
DOI: 10.1111/j.1399-6576.2009.02031.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional anticoagulation and antiaggregation for CVVH in critically ill patients: a prospective, randomized, controlled pilot study

Abstract: In critically ill patients suffering from acute renal failure, regional anticoagulation with pre-filter heparin and post-filter protamine plus antiaggregation during CVVH is a simple and safe procedure that prevents increases in filter TMP and increases circuit life time compared with systemic anticoagulation with pre-filter heparin only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…A few small trials showed improved filter survival during CRRT when adding prostaglandins to heparin compared with heparin alone [95-97]. However, prostaglandins appear to have a limited efficacy when used alone, induce systemic hypotension [98,99], and are expensive.…”
Section: Recommendations and Rationalementioning
confidence: 99%
“…A few small trials showed improved filter survival during CRRT when adding prostaglandins to heparin compared with heparin alone [95-97]. However, prostaglandins appear to have a limited efficacy when used alone, induce systemic hypotension [98,99], and are expensive.…”
Section: Recommendations and Rationalementioning
confidence: 99%
“…Of these, 157 were excluded on the basis of titles and abstracts, because they were reviews, observational studies, retrospective studies, case reports, and other irrelevant studies. Of the remaining 10 articles, four were excluded after assessment of the full-text article, because two were nonrandomized sequential trials [8,11], one used regional heparin anticoagulation as the treatment group [12], and one allocated patients to the citrate group because they had contraindications for systemic heparin administration [13]. As a result, a total of six studies [14][15][16][17][18][19] were finally included into the meta-analysis (Fig.…”
Section: Study Enrollment and Characteristicsmentioning
confidence: 99%
“…One such study compared the use of pre-filter heparin and prostacyclin with post-filter protamine sulfate versus pre-filter heparin alone in CVVH. The filter transmembrane pressure rise was used to detect filter clotting, a significant rise of which was seen in the group on heparin anticoagulation alone [8]. A study of pre- versus post-dialyzer pressure differences in intermittent hemodialysis concluded that such differences could not significantly unmask subclinical clotting resulting in inefficient hemodialysis [12].…”
Section: Discussionmentioning
confidence: 99%
“…Most modern CRRT machines are equipped with pressure sensors, and many studies allude to their reliance on pressure readings to prompt interventions such as change of circuit. The transmembrane pressure has been used to diagnose clotting when comparing two anticoagulation methods during continuous venovenous hemofiltration (CVVH) [8]. Similar studies also adopted extracorporeal line pressure readings rising above 250 mm Hg as an acceptable surrogate for hemofilter clotting [9].…”
Section: Introductionmentioning
confidence: 99%